Socio-economic determinants of the family history of pulmonary tuberculosis patients in Pakistan. Issue 1 (2nd January 2019) - Saqib, Shahab E.; Ahmad, Mokbul Morshed
ABSTRACT: This article aims to assess the role of important socio-economic factors in the family history of tuberculosis patients in Pakistan. Data were collected from 269 patients, and a logistic regression was used to determine the association between risk factors and the vicious circle of TB. Results of the logistic model show that significant risk factors associated with TB history in patients were education, household size, house structure, rooms in the home, room ventilation, monthly income, income food sufficiency, smoking, diabetes, and heart disease. The current TB control programme needs to formulate strategies to target specific risk factors and poverty reduction simultaneously to break the vicious circle of tuberculosis.